1993
DOI: 10.1118/1.597106
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray sources of medical linear accelerators: Focal and extra‐focal radiation

Abstract: A computerized tomography (CT) reconstruction technique has been used to make quantitative measurements of the size and shape of the focal spot in medical linear accelerators. Using this technique, we have measured the focal spots in a total of nine accelerators, including (i) two Varian Clinac 2100c's, (ii) two Atomic Energy of Canada Ltd. (AECL) Therac-25's, (iii) two AECL Therac 6's, (iv) a Siemens KD-2, (v) a Varian Clinac 600c (4 MV), and (vi) an AECL Therac-20. Some of these focal spots were monitored fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
176
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(195 citation statements)
references
References 0 publications
17
176
1
1
Order By: Relevance
“…A small but consistent change (1%–2%) in OF was observed, with the highest reading at 90°. This observation agreed with previous work of Scott et al (35) and Jaffray et al, (36) where a spot size slightly larger in the Y direction was reported.…”
Section: Discussionsupporting
confidence: 94%
“…A small but consistent change (1%–2%) in OF was observed, with the highest reading at 90°. This observation agreed with previous work of Scott et al (35) and Jaffray et al, (36) where a spot size slightly larger in the Y direction was reported.…”
Section: Discussionsupporting
confidence: 94%
“…For fields smaller than 2×2 cm2, the size of the direct source affects dosimetry parameters such as output factor, beam profiles, and percent depth doses 3 , 4 . This is a problem because it has also been observed that different accelerators, or different energies on the same accelerator, have different source sizes (11) . Consequently, the development of a standard dataset for output factors of field sizes smaller than 2×2 cm2 may be impossible.…”
Section: Resultsmentioning
confidence: 99%
“…It was decided not to investigate radii below 0.05 cm, as values below this are unrealistic. ( 17 ) The water phantom voxels were set to 1×1×1cm3 for the measurement of the dose profiles at 1.5 cm depth. This somewhat large voxel size was employed to keep simulation time to a minimum so as to perform quick simulations to narrow the estimation of the energy range.…”
Section: Resultsmentioning
confidence: 99%